The effect of formative assessment on the achievement of first-stage students in the planning subject (Journal of the College of Basic Education, 2022)
Evaluation is one of the most important elements of the pedagogical system and one of the main pillars in the processThe educational - the educational knowledge of its basic relationship with the objectives and competencies ruled in addition to being the criterionTo diagnose the strengths and weaknesses of our pedagogical system and our reform experiences in the field of educationEducation has become, in recent years, a prominent place in the circle of educational sciences, almost a field celebratedIt has its own scientific subject and methodological tools.This growing importance of the calendar in our time is due to special factors. Among them :The development of educational systems in modern and contemporary societies, interest in the economics of education and developmentresults in the educational field